Correlation of diaphragm thickening fraction and oesophageal pressure swing in non-invasive ventilation of healthy subjects - Lindner, Simon; Hoermann, Clara; Teichert, Jan; Ziyadova, Sevil; Michels-Zetsche, Julia D.; Neetz, Benjamin; Herth, Felix J. F.; Duerschmied, Daniel; Britsch, Simone (BMC pulmonary medicine, 2024)
The diaphragm thickening fraction (DTF) may be a valuable tool for estimating respiratory effort in non-invasive ventilation. The primary aim of this physiological study is the investigation of the correlation of DTF with oesophageal pressure swings (ΔP ). A secondary aim is to assess the discriminatory capacity of the index tests for different exercise loads. Healthy volunteers underwent spontaneous breathing and non-invasive ventilation with a sequence of different respirator settings. The first sequence was carried out at rest. The same sequence was repeated twice, with additional ergometry of 25 and 50 Watts, respectively. DTF and ΔP were measured during each ventilation configuration. 23 individuals agreed to participate. DTF was moderately correlated with ΔP (repeated measures correlation ρ = 0.410, p < 0.001). Both ΔP and DTF increased consistently with exercise loading in every ventilation configuration, however ΔP showed greater discriminatory capacity. DTF was moderately correlated with ΔP and could discriminate reasonably between exercise loads in a small cohort of non-invasively ventilated healthy subjects. While it may not accurately reflect the absolute respiratory effort, DTF might help titrating individual non-invasive respiratory support. Further investigations are needed to test this hypothesis. This study was not prospectively registered.